Constructing Chemical Interaction between Hematite and Carbon Nanosheets with Single Active Sites for Efficient Photo‐Electrochemical Water Oxidation. Issue 12 (13th September 2020) - Yang, Gaoliang; Li, Yunxiang; Lin, Huiwen; Ren, Xiaohui; Philo, Davin; Wang, Qi; He, Yu; Ichihara, Fumihiko; Luo, Shunqin; Wang, Shengyao; Ye, Jinhua
Abstract: Addressing the intrinsic charge recombination of hematite (α‐Fe2 O3 ) is significantly important for achieving highly efficient photo‐electrochemical water oxidation but still remains challenging. Herein, this challenge is tackled by constructing chemical interaction at the interface of α‐Fe2 O3 and carbon nanosheets with single‐nickel sites (Ni‐NC), which can accelerate the reaction kinetics by providing additional charge transport channels and abundant active sites. The interfacial carrier path induced by the chemical coupling and the efficient single‐nickel sites work collaboratively, achieving an impressive photocurrent density of 1.85 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE), up to 2.2 times higher than that of pure α‐Fe2 O3 . These findings shed light on an interface modulation strategy and provide an alternative toward utilizing unique single active sites for efficient photo‐electrochemical water splitting. Abstract : This study demonstrates an efficient photo‐electrochemical (PEC) water oxidation system with strong interfacial chemical interaction between hematite and carbon nanosheets with single‐nickel sites. The chemical coupling can facilitate charge carrier transfer occurring at the interface and the isolated Ni active sites can fully utilize the collected holes from α‐Fe2 O3, hence achieving an impressive PEC water oxidation activity.